Legal nature of regulative decisions of the Constitutional Court of the Republic of Kazakhstan: comparative legal analysis - Junussova М.Т.; Kalybaeva А.А.; Shauali М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The determination of the legal nature of the normative resolutions of the Constitutional Court of the Republic of Kazakhstan is an important aspect of defining the boundaries of the national legal system. The relevance of the study is enhanced by the adoption of the new Constitution of the Republic of Kazakhstan at the republican referendum on 15 March 2026, which necessitates a reconsideration of the role of constitutional review and the legal significance of the decisions of the Constitutional Court of the Republic of Kazakhstan. The article examines the legal nature of the normative resolutions of the Constitutional Court, their impact and legal consequences in the context of Kazakhstan based on a comparative legal analysis. The study analyzes the binding nature of the Constitutional Court’s decisions, the mechanisms of their implementation, as well as their influence on the legislative, executive and judicial branches of power. In addition, the place and significance of these decisions within the system of legal regulation are determined. By comparing the practice of constitutional courts of foreign states, similarities and differences are identified, and the impact of such acts on the formation and development of the legal system is assessed. The study substantiates the dual legal nature of the Constitutional Court’s decisions as both a source of law and an act of law enforcement. It formulates their role and significance in legal regulation.